Enhancing Security and Efficiency in IoT through Edge Computing - Bhat, Aaqib Nisar; Malik, Nisar Ahmad (Trends in Computer Science and Information Technology, 2025)
The Internet of Things (IoT) has witnessed exponential growth, with billions of connected devices generating vast amounts of data. However, this proliferation of IoT devices has raised significant concerns regarding security and operational efficiency. This research paper explores the integration of edge computing as a strategic solution to address these challenges. The study delves into the existing literature on IoT security and efficiency, identifying gaps that necessitate further investigation. Our methodology involves a comprehensive examination of security threats in IoT ecosystems and an exploration of the role of edge computing in mitigating these risks. The paper outlines the definition and significance of edge computing in the context of IoT, emphasizing its potential to minimize data exposure and enhance operational efficiency. A case study exemplifies the application of edge computing, illustrating its impact on security and efficiency in a real-world IoT environment. Results and findings demonstrate the positive influence of edge computing on bolstering security measures and optimizing operational performance. The discussion interprets these findings within the broader research landscape, outlining implications and potential contributions to the field. Despite the advancements presented, the paper acknowledges limitations and suggests avenues for future research. In conclusion, the study underscores the critical importance of addressing security and efficiency concerns in IoT through the strategic implementation of edge computing, providing valuable insights for researchers, practitioners, and policymakers alike.